The conjuring - WETMORE, KEVIN J. (LIVERPOOL UNIV PRESS, 2021)
In 2013 an apparently simple, back-to-basics scary movie transformed horror cinema for the rest of the decade. Based on the allegedly true story of the Perron family haunting and subsequent investigation by ghost hunters Ed and Lorraine Warren, The Conjuring has to-date spawned six sequels and prequels, making up a Conjuring 'universe' that has taken over a billion dollars around the world. The New York Times called The Conjuring 'a fantastically effective haunted-house movie' which, following his earlier film Insidious, established director James Wan as a force in horror cinema. In this Devil's Advocates, horror scholar Kevin Wetmore examines what elements in the film are truly terrifying, how the filmmakers' claims of being based on a true story hold up against the actual history of the haunting and the Warrens, and the relationship between The Conjuring and the many films in its universe. Along the way this book also considers how games, toys and dolls play an important role in ...